A whole new vigor: About Montel’s book "Les mathématiques et la vie" (1947) - Mazliak, Laurent (Teaching Mathematics and Computer Science, 2020)
In this paper, we consider a talk presented by the mathematician Paul Montel in Paris in 1944, dedicated to a general presentation of the importance of mathematics in everyday’s life. The text of this talk, and the context of its elaboration, allows various inceptions in the French mathematical life in the middle of 20th century. In particular Montel’s insistence on applications of mathematics strongly contrasts with the main tendencies of the French mathematical stage after the war under the impulse of the Bourbaki group. Subject Classification: 97A40, 01A60, 60-03